Application of quantitative PCR method in detection of Lymphocystis disease virus China （LCDV-cn） in Japanese flounder （Paralichthys olivaceus） - 昝金东 孙修勤 张之文 曲凌云 张进兴 (Chinese journal of oceanology and limnology, 2007)
Lymphocystis disease causes serious economic losses in the fish farming industry. The causative agent of the disease is Lymphocystis disease virus China （LCDV-cn）, which has a wide range of hosts. Based on competitive quantitative PCR technology, we established a method to quantify the LCDV-cn in tissue. Results demonstrate that the average amount of LCDV-cn in the peripheral blood of infected flounder with evident tumors is about 10^6virions/ml while the average amount in those flounder with no evident tumor but cultured with the flounder with evident tumor is about 10^4virions/ml. No virus was found in the negative samples of flounder.